Short‐tailed temperature distributions over North America and implications for future changes in extremes. Issue 20 (23rd October 2015) - Loikith, Paul C.; Neelin, J. David
Abstract: Some regions of North America exhibit nonnormal temperature distributions. Shorter‐than‐Gaussian warm tails are a special subset of these cases, with potentially meaningful implications for future changes in extreme warm temperatures under anthropogenic global warming. Locations exhibiting shorter‐than‐Gaussian warm tails would experience a greater increase in extreme warm temperature exceedances than a location with a Gaussian or long warm‐side tail under a simple uniform warm shift in the distribution. Here we identify regions exhibiting such behavior over North America and demonstrate the effect of a simple warm shift on changes in extreme warm temperature exceedances. Some locations exceed the 95th percentile of the original distribution by greater than 40% of the time after this uniform shift. While the manner in which distributions change under global warming may be more complex than a simple shift, these results provide an observational baseline for climate model evaluation. Key Points: Many locations have non‐Gaussian temperature distributions Some locations have short warm‐side tails Places with short tails may experience a large increase in warm extremes